2009
DOI: 10.1785/0120080133
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of NGA Ground-Motion Prediction Equations to Italian Data

Abstract: Ground-motion prediction equations (GMPEs) have recently been developed in the Next Generation Attenuation (NGA) project for application to shallow crustal earthquakes in tectonically active regions. We investigate the compatibility of those models with respect to magnitude scaling, distance scaling, and site scaling implied by Italian strong motion data. This is of interest because (1) the Italian data are principally from earthquakes in extensional regions that are poorly represented in the NGA dataset, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 30 publications
11
95
0
Order By: Relevance
“…These authors indicated that the regional differences in ground-motion estimates would be prominent towards smaller magnitude earthquakes, which is a parallel observation with the studies conducted in the other parts of the world (Chiou et al 2010;Atkinson and Morrison 2009). On the other hand, Scasserra et al (2009) emphasized that the use of NGA-West1 GMPEs may over predict the hazard in Italy at large distances because Italian data attenuate faster than the trends depicted in NGA-West1 GMPEs. In a separate study, who developed a GMPE from an extended Turkish database showed that NGA-West1 GMPEs and ground-motion predictive models from pan-European datasets would yield conservative estimates with respect to their GMPE for different earthquake scenarios at different spectral ordinates.…”
Section: Introductionsupporting
confidence: 54%
“…These authors indicated that the regional differences in ground-motion estimates would be prominent towards smaller magnitude earthquakes, which is a parallel observation with the studies conducted in the other parts of the world (Chiou et al 2010;Atkinson and Morrison 2009). On the other hand, Scasserra et al (2009) emphasized that the use of NGA-West1 GMPEs may over predict the hazard in Italy at large distances because Italian data attenuate faster than the trends depicted in NGA-West1 GMPEs. In a separate study, who developed a GMPE from an extended Turkish database showed that NGA-West1 GMPEs and ground-motion predictive models from pan-European datasets would yield conservative estimates with respect to their GMPE for different earthquake scenarios at different spectral ordinates.…”
Section: Introductionsupporting
confidence: 54%
“…There are no strong-motion recordings in South Africa, precluding the possibility of deriving empirical GMPEs for South Africa or using the so-called referenced empirical approach (Atkinson, 2008;Scasserra et al, 2009). After opting not to attempt to derive new stochastic GMPEs for South Africa within the timeframe of the Thyspunt PSHA study, the GMC team applied a variant of the hybridempirical approach (Campbell, 2003) for the development of appropriate GMPEs for use in the PSHA.…”
Section: Overview Of the Gmc Modelmentioning
confidence: 99%
“…We infer approximate R JB values from these parameters, guided by the R rup and R JB simulation results from Chiou and Youngs (2006). To calculate the depth to the top of the rupture plane Z TOR , the down-dip rupture width is estimated from H, M w , and focal mechanism, using the relation of Wells and Coppersmith (1994), and Z TOR is approximated as half the down-dip rupture width, following Scasserra et al (2009) andBradley (2013). For these scenarios, we calculate response spectra for each seismic station previously analyzed in this study, using the site information given in Table 1.…”
Section: Applicationmentioning
confidence: 99%